2016
DOI: 10.1016/j.jff.2015.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laboratory-scale decoction on the antioxidative activity of Zhenjiang Aromatic Vinegar: The contribution of melanoidins

Abstract: Decoction, the characteristic heat-treatment procedure in Zhenjiang Aromatic Vinegar (ZAV) processing, was performed in laboratory to investigate its effect on the antioxidative activity (AA) of ZAV. Owing to the laboratory-scale decoction, DPPH radical scavenging activity, ORAC value and cellular antioxidant activity (CAA) of ZAV increased by 63, 24 and 54% of that of undecocted vinegar, respectively. Enzymatic assay and HPLC determination proved that phenolic content decreased after the decoction, while mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…Liu et al. demonstrated that melanoidins accounted for 57.1% and 44.1% of the total antioxidant activity in Zhenjiang aromatic vinegar by 1,1‐diphenyl‐2‐picrylhydrazyl and oxygen radical absorbance capacity assays (Liu et al., ). In our previous study, we found that the antioxidant activities of SAV in smoking pei stage increased more obviously than that in the stages of alcoholic fermentation and acetic acid fermentation due to the increase of phenols and flavonoids (Xie et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al. demonstrated that melanoidins accounted for 57.1% and 44.1% of the total antioxidant activity in Zhenjiang aromatic vinegar by 1,1‐diphenyl‐2‐picrylhydrazyl and oxygen radical absorbance capacity assays (Liu et al., ). In our previous study, we found that the antioxidant activities of SAV in smoking pei stage increased more obviously than that in the stages of alcoholic fermentation and acetic acid fermentation due to the increase of phenols and flavonoids (Xie et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…After leaching the process, a decoction process is conducted to pasteurize the vinegar before further storage. During this step, a series of reactions may occur like the Maillard reaction, decomposition, degradation and esterification 13,14,32 .…”
Section: Resultsmentioning
confidence: 99%
“…However, Fraglide-1 has not been determined in an aroma analysis of Kozu vinegar in the literature. It was shown that wheat husk can normally be used for Zhenjiang vinegar production 32 . The…”
Section: Resultsmentioning
confidence: 99%
“…Melanoidins were obtained as reported earlier (Bekedam et al ., ; Liu et al ., ), and after filtering through a Whatman no. 4 filter paper, 100 mL solution was thoroughly mixed with 40 mL ethanol and subjected to centrifugation.…”
Section: Methodsmentioning
confidence: 99%